Strategic Thinking: - Windsor, Philip (Lynne Rienner Publishers, 2002)
This debate-style reader is designed to introduce students to controversies in justice and law through readings that reflect a variety of viewpoints. Each issue is framed with an issue summary, an issue introduction, and a postscript. The Taking Sides readers feature annotated listings of selected World Wide Web sites. Taking Sides is supported by our student website, Dushkin Online